Tetrafluoroethylene and perfluoroalkyl vinyl ether copolymer resin and preparation method thereof
By using fluorine carboxylate containing 6-8 carbon atoms as emulsifier, a high-purity copolymer resin of tetrafluoroethylene and perfluoroalkyl vinyl ether was prepared, which solved the problems of traditional emulsifier residues and uneven molecular weights, and achieved the Preparation of fluororesin with low residue and high purity.
Patent Information
- Application Number
- CN202311011994.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-08-11
AI Technical Summary
The prior art is difficult to avoid emulsifier residues when preparing high-purity fluororesins, especially PFOA is limited due to its environmental durability and biotoxicity, and traditional emulsifiers have problems of structural control and uneven polymer molecular weight.
Fluorinated carboxylic acids and salts with 6-8 carbon counts and 1-4 ether oxygen atoms in the main chain are used as emulsifiers to prepare stable The polymer emulsion is used to obtain a fluororesin with a low residual amount of emulsifier through processes such as coagulation, washing, and drying.
The residual amount of fluorine-containing emulsifier is achieved below 0.2ppm, meeting the demand for high-purity fluorine resins in semiconductors, medical and other fields, and improving washing efficiency and production efficiency.
Smart Images

Figure BDA0004390466540000101 
Figure BDA0004390466540000111
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fluorine-containing resins and relates to a tetrafluoroethylene and perfluoroalkyl vinyl ether copolymer resin and a preparation method thereof. Background Art
[0002] Tetrafluoroethylene (hereinafter referred to as TFE) homopolymer and its copolymer have outstanding properties such as outstanding heat resistance, chemical corrosion resistance, weather resistance, low flammability and low surface energy. They can be used as functional films, cable insulation protective layers, corrosion-resistant coatings and seals, etc. They are often used in aerospace, automotive industry, electronic information and new energy fields to resist harsh application environments and play a special role.
[0003] Polytetrafluoroethylene (PTFE) or modified PTFE emulsion can be prepared by aqueous emulsion polymerization of fluorinated monomers such as TFE. Fluororesins in the form of powders and the like can be obtained by further coagulation and drying of the emulsion, which are used as raw materials for various molded objects. This polymerization method generally uses a fluorinated emulsifier, usually ammonium perfluorooctanoate (structural formula CF3(CF2)6COONH4, PFOA for short), whose main chain consists of only 8 carbon atoms. However, if the emulsifier remains in the fluororesin material, it will not be able to meet the applications in semiconductors, medical and other fields that have particularly high requirements for purity. Not only that, PFOA has been gradually controlled globally due to its extremely strong environmental persistence, bioaccumulation, long-distance migration ability and biological toxicity, and has been included in Annex A of the POPs Convention in 2020.
[0004] In view of the above problems, a solution of washing or refining the fluororesin emulsion by ion exchange or the like was proposed in the early stage to obtain a fluororesin with higher purity. With the advancement of technology and the enhancement of people's environmental awareness, technicians in this field are more eager to provide a solution that does not contain PFOA or uses a new emulsifier to achieve the purpose of not containing PFOA or low emulsifier residue in the polymer. Chinese patent document CN1505644A provides a method for preparing tetrafluoroethylene homopolymer or copolymer without emulsifier. However, the particle size of the fluoropolymer emulsion prepared by this method is about 500nm, which is 3-5 times the particle size of the emulsifier system, and the emulsion stability is poor. Chinese patent document CN102264684A proposes a technology for preparing fluoropolymers using partially fluorinated carboxylates containing one or more ethylene-tetrafluoroethylene parts (-CH2CH2CF2CF2-) as emulsifiers, but the above-mentioned partially fluorinated carboxylates have the problem of difficult structural control during the preparation process, and the H atoms on the molecular chain of the emulsifier have a strong chain transfer tendency, resulting in the problem that the polymer molecular weight is not high enough and the molecular weight distribution is uneven; at the same time, there are also problems such as low solid content of the polymer emulsion, only 15-16wt%, low production efficiency and high manufacturing cost. Patent CN106084104A provides a method for preparing PTFE resin emulsion using perfluorohexanoate as an emulsifier, but perfluorohexanoic acid is a compound containing a longer perfluoro chain segment, and its use as an emulsifier has been restricted due to its bioaccumulation and difficulty in degradation. Patent CN101296950A uses a specific CF3CF2OCF2CF2OCF2COONH4 (EEA) structured emulsifier to prepare a fluoropolymer emulsion. This patent uses the emulsifier to prepare PTFE homopolymer emulsion, and the emulsifier has a short straight chain group with only 6 carbon atoms in the main chain. However, it has the disadvantage of low solid content of the emulsion, and the residual emulsifier in the resin is still relatively high, which is not conducive to applications in fields with high requirements for low residual content. Summary of the invention
[0005] The object of the present invention is to provide a fluororesin having a small environmental load, being free of PFOA, and having a small amount of residual fluorinated emulsifier compared to PFOA, and a method for preparing the same. The inventors have found that a stable polymer emulsion can be obtained by selecting one or more fluorinated emulsifiers of fluorinated carboxylic acids and their salts having 6 to 8 carbon atoms and 1 to 4 etheric oxygen atoms in the main chain to carry out emulsion polymerization of TFE and perfluoroalkyl vinyl ether monomer (hereinafter referred to as PAVE). The emulsion can be further used to prepare fluorinated polymer powder or molten particles by processes such as coagulation, washing, drying, pulverization or granulation.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A tetrafluoroethylene and perfluoroalkyl vinyl ether copolymer resin (PFA), comprising a tetrafluoroethylene structural unit (TFE unit) and a perfluoroalkyl vinyl ether structural unit (PAVE unit), wherein the molar ratio of the TFE unit to the PAVE unit is 70-99.5 / 30-0.5;
[0008] The resin is prepared by copolymerizing tetrafluoroethylene and PAVE monomers in an aqueous medium using a fluorinated emulsifier represented by formula (1), and then condensing, washing and drying the emulsion. The residual amount of the fluorinated emulsifier represented by formula (1) in the resin is less than 0.2 ppm.
[0009] The emulsifier structure is shown in the general formula (1): f1 (OCF2) x -(OR f2 ) y -OCF(CF3)COOA, in formula (1), the R f1 is a perfluoro straight-chain alkyl group having 1 to 2 carbon atoms, R f2 It is a perfluorinated straight chain or side chain alkyl group having 2 to 3 carbon atoms, x and y are each independently 0 or 1, and x and y are not simultaneously 0, and A is a hydrogen atom, an alkali metal or NH4. More preferably, A is NH4.
[0010] This type of resin can solve the problem of high-purity fluorine-containing resins that are actually free of PFOA, which is required in the semiconductor, medical and other fields.
[0011] The fluorinated emulsifier of formula (1) has good emulsion stabilization effect and low chain transfer tendency to monomer free radicals, and the residual amount of fluorinated emulsifier in the obtained polymer is 0.2 ppm or less. Preferably, the residual amount of emulsifier in the fluororesin is less than 50 ppb, and more preferably less than 25 ppb.
[0012] Further preferably, the fluorinated emulsifier comprises:
[0013] (a)CF3OCF2CF2OCF(CF3)COONH4,
[0014] (b)CF3OCF2OCF2CF2OCF(CF3)COONH4,
[0015] (c) one of CF3CF2OCF(CF3)CF2OCF(CF3)COONH4 and their combinations.
[0016] In particular, the above-mentioned preferred fluorinated carboxylic acid containing etheric oxygen atoms and its salt or its composition with a total carbon number of 6 to 8 has a similar perfluoroether bond structure to PAVE, thereby having better solubility and dispersion effect on it. On the one hand, it can achieve a higher solubility concentration in the reaction phase under low PAVE addition conditions, which is beneficial to reducing the amount of PAVE added. On the other hand, it is particularly beneficial to obtain PFA polymers with uniform segment distribution; at the same time, compared with PFOA, due to the presence of etheric oxygen atoms or shorter carbon fluorine segments, the obtained fluororesin latex particles have better water wettability, thereby achieving the effect of using less washing water to achieve lower emulsifier residues in the post-treatment process, and improving the washing efficiency. This effect is particularly beneficial to commercial production.
[0017] Preferably, the molar ratio of TFE units to PAVE units in the resin is 80-99 / 20-1, more preferably 90-98 / 10-2, and further preferably 96-98 / 2-4. If there are too few PAVE monomer units, the melting point is too high and there is a tendency for reduced moldability. If there are too many PAVE monomer units, there is a tendency for reduced mechanical properties and reduced temperature resistance. The method of adding the PAVE monomer is not particularly limited. It can be added once before the reaction or added continuously or intermittently during the reaction process. From the perspective of improving the uniformity of the resin structure, it is preferred to use a continuous addition method during the reaction process.
[0018] The melt index (MFR) of the PFA resin is 0.1 to 100 g / 10 min, preferably 0.5 to 80 g / 10 min, and more preferably 1 to 30 g / 10 min. The particle size of the emulsion is 250 to 290 nm.
[0019] Preferably, the PFA resin further comprises a monomer unit copolymerizable with TFE and PAVE, and the molar percentage of the monomer unit in the PFA resin structural unit is 0.1-10%. The monomer copolymerizable with TFE and PAVE may be hexafluoropropylene (HFP) or the like.
[0020] Preferably, the PAVE monomer has the general structural formula: CF2=CF-OR f3 (2)
[0021] In the formula, R f3It is a straight-chain perfluoroalkyl group or a branched perfluoroalkyl group having 1 to 6 carbon atoms. Examples of such comonomers may include CF2=CF-O-CF3 (PMVE), CF2=CF-O-CF2-CF3 (PEVE), and CF2=CF-O-CF2-CF2-CF3 (PPVE); preferably, CF2=CF-O-CF2-CF3 (PEVE) or CF2=CF-O-CF2-CF2-CF3 (PPVE). One of them or a combination thereof may be used in the polymerization.
[0022] The present invention also provides a copolymer emulsion containing the above-mentioned tetrafluoroethylene and perfluoroalkyl vinyl ether copolymer resin (PFA) resin, and the solid content of the copolymer resin in the emulsion can be 8-38%. Considering the emulsion stability, resin molecular weight uniformity and commercialization cost, it is preferably 10-35%, and more preferably 20-30%.
[0023] The present invention provides a method for preparing the above-mentioned tetrafluoroethylene and perfluoroalkyl vinyl ether copolymer resin (PFA), comprising the following steps: in the presence of an aqueous medium, an emulsifier, a free radical polymerization initiator and a molecular weight regulator, emulsion polymerization is performed on TFE and PAVE copolymer monomers, and the prepared copolymer emulsion is subjected to coagulation, washing and drying processes to obtain PFA resin powder.
[0024] Preferably, the amount of the emulsifier is usually 500-15000ppm, preferably 1000-12000ppm, more preferably 2000-10000ppm, and most preferably 3000-5000ppm based on the mass of the PFA polymer finally obtained. There is no particular restriction on the way of adding the emulsifier, which can be added once before the reaction, or continuously or intermittently during the reaction.
[0025] There are no particular restrictions on the free radical initiator used in the emulsion polymerization of the tetrafluoroethylene and perfluoroalkyl vinyl ether copolymer resin (PFA), and examples thereof include water-soluble redox initiators, including but not limited to persulfate systems, such as ammonium persulfate, potassium persulfate or sodium persulfate, and reducing agents such as sodium sulfite, sodium pyrosulfite, sodium thiosulfate, peroxide systems, such as disuccinic acid peroxide, diglutaric acid peroxide, tert-butyl peroxide, etc., manganate systems, such as permanganate compounds, and in order to improve the initiation efficiency, oxalic acid, ascorbic acid, etc. can also be used as reducing agents, azo salt compounds such as azobisisobutylamidine dihydrochloride, azobisisopropylimidazoline hydrochloride, etc.
[0026] The amount of the initiator added is preferably 50-5000 ppm, more preferably 50-1000 ppm, relative to the total mass of the polymerizable monomers. The initiator can be added in any manner, and can be added at the beginning of the emulsion polymerization or in the middle of the emulsion polymerization.
[0027] As a chain transfer agent used in the emulsion polymerization of tetrafluoroethylene and perfluoroalkyl vinyl ether copolymer resin (PFA), it can be used to adjust the molecular weight of the polymer. The preferred chain transfer agent can be alcohol, such as methanol or ethanol; chlorofluorocarbon, such as 1,3-dichloro-1,1,2,2,3-pentafluoropropane or 1,1-dichloro-1-fluoroethane; or hydrocarbon, such as methane, ethane, propane, pentane, cyclohexane; or ethers, such as dimethyl ether, tert-butyl ether, methyl tert-butyl ether, etc.
[0028] The amount of the chain transfer agent added is preferably 10-15000 ppm, more preferably 100-12000 ppm, relative to the total weight of the polymerized monomers. The chain transfer agent can be added in any manner, and can be added at the beginning of the emulsion polymerization or in the middle of the emulsion polymerization.
[0029] The conditions for the emulsion polymerization of tetrafluoroethylene and perfluoroalkyl vinyl ether copolymer resin (PFA) can be appropriately selected according to the type of monomers used, the decomposition temperature of the initiator, etc. The emulsion polymerization temperature is preferably 10-95° C., more preferably 30-80° C. The polymerization pressure is preferably 0.5-4.0 MPa, more preferably 0.6-3.5 MPa. The polymerization time is preferably 50-600 minutes, more preferably 90-480 minutes.
[0030] The coagulation method of the tetrafluoroethylene and perfluoroalkyl vinyl ether copolymer resin (PFA) emulsion is not particularly limited, and examples thereof include strong mechanical stirring coagulation, adding a coagulant, or freezing the emulsion. The method using a coagulant is preferred.
[0031] The coagulant may include water-soluble salts such as sodium chloride, calcium chloride, magnesium chloride, etc.; inorganic acids such as nitric acid, hydrochloric acid, sulfuric acid, etc.; organic compounds such as ethanol, acetone, etc. The amount of the coagulant added is 0.01-20% relative to the mass of the copolymer emulsion, more preferably 0.01-10%.
[0032] The condensed PFA resin is washed with deionized water and then dried to prepare polymer powder. The drying method may be vacuum drying, hot air drying, etc. The drying temperature is preferably 30-230°C, more preferably 100-230°C.
[0033] Beneficial effects of the present invention:
[0034] The tetrafluoroethylene and perfluoroalkyl vinyl ether copolymer resin (PFA) prepared by the present invention has a lower residual fluorinated emulsifier, less than 15 ppb, and can be further screw extruded to produce resin particles or solvent granulated or roller granulated to produce coating powder, etc., which can be used as a raw material for cable coatings, injection molded parts, tubes, films and coated parts, as well as optical parts and other molded bodies. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below with reference to the embodiments, but the present invention is not limited to these embodiments.
[0036] Test method:
[0037] (1) Monomer unit content test: The monomer unit content of the PFA resin is calculated based on the monomer type combined with NMR, FTIR, elemental analysis and other analysis.
[0038] (2) Emulsion particle size: The PFA emulsion particle size was tested and characterized using a scanning electron microscope-energy dispersive spectrometer (SEM-EDS).
[0039] (3) Melting point: The melting point of the PFA resin is the temperature corresponding to the maximum value on the melting heat curve at a heating rate of 10° C. / min under a nitrogen atmosphere using a differential scanning calorimeter (DSC).
[0040] (4) Melt Index: The MFR of the PFA is determined by referring to the method of ASTM D 3307. The melt flow rate is the mass of the resin that flows out of the die at 372°C, 5 kgf load, and a die diameter of 2.1 mm and length of 8 mm for 10 minutes.
[0041] (5) Residual amount of fluorinated emulsifier: Accurately weigh 5 portions of 1g powder sample, place them in 5 clean glass vials with lids and add 3ml of extraction solvent, where the extraction solvent consists of 80 parts of methanol and 20 parts of ammonium acetate-acetic acid solution (solution concentration 20mmol / L); seal the sample vials and place them in a shaker, shake and extract for 1h at a frequency of 250 rpm and 40°C. After filtering the extract through an organic microporous membrane, place it in a liquid phase injection bottle for LC-MSMS liquid chromatography-mass spectrometry detection. Use the standard solution curve to determine the fluorinated emulsifier content of the sample to be tested.
[0042] The emulsifiers used in the specific embodiments and comparative examples of the present invention are as follows:
[0043] (a)CF3OCF2CF2OCF(CF3)COONH4,
[0044] (b)CF3OCF2OCF2CF2OCF(CF3)COONH4,
[0045] (c)CF3CF2OCF(CF3)CF2OCF(CF3)COONH4,
[0046] (d)CF3CF2CF2OCF(CF3)CF2OCF(CF3)COONH4,
[0047] (PFOA)CF3CF2CF2CF2CF2CF2CF2COONH4,
[0048] (EEA)CF3CF2OCF2CF2OCF2COONH4.
[0049] Example 1
[0050] Add 3L of deionized water and 20g of CF3OCF2CF2OCF(CF3)COONH4(a) aqueous solution with a mass concentration of 20% to a 5L stainless steel autoclave equipped with a stirring and temperature control device, and repeatedly evacuate and replace with nitrogen until the oxygen content is below 10ppm. Add 10g of methanol, heat to 60°C, add TFE to the system until the pressure reaches 2.0MPa, and add 48g of PPVE monomer with a metering pump. Add 10g of 2g / L ammonium persulfate solution to the polymerization kettle to initiate the polymerization reaction. After the reaction starts, continue to add TFE monomer and PPVE monomer to maintain the polymerization pressure of 2.0MPa, and continue to add ammonium persulfate solution at a rate of 0.15g / min. The polymerization reaction is stopped after 2.5 hours, during which 80g of PPVE monomer and 860g of TFE monomer are added cumulatively, and the unreacted monomers in the kettle are emptied to obtain an emulsion with a solid content of 23.6%. According to SEM-EDS testing, the average particle size of the emulsion is 256nm.
[0051] The PFA emulsion after the reaction was condensed, washed with water, and dried to obtain 980g of PFA resin powder. The PFA melt index was measured to be 16.8g / 10min using a melt index meter, the melting point was measured to be 302°C using a differential scanning calorimeter DSC, and the TFE / PPVE content (mol ratio) in the PFA polymer was measured to be 97.5 / 2.5 using infrared FT-IR. The fluorine-containing emulsifier content in the PFA powder was tested to be 10.2ppb.
[0052] Example 2
[0053] Add 3L of deionized water and 20g of CF3OCF2OCF2CF2OCF(CF3)COONH4(b) aqueous solution with a mass concentration of 20% to a 5L stainless steel autoclave equipped with a stirring and temperature control device, and repeatedly evacuate and replace with nitrogen until the oxygen content is below 10ppm. Add 10g of methanol, heat to 60°C, add TFE to the system until the pressure reaches 2.0MPa, and add 52g of PPVE monomer with a metering pump. Add 10g of 2g / L ammonium persulfate solution to the polymerization kettle to initiate the polymerization reaction. After the reaction starts, continue to add TFE monomer and PPVE monomer to maintain the polymerization pressure of 2.0MPa, and continue to add ammonium persulfate solution at a rate of 0.15g / min. The polymerization reaction is stopped after 2.5 hours, during which 108g of PPVE monomer and 900g of TFE monomer are added cumulatively, and the unreacted monomers in the kettle are emptied to obtain an emulsion with a solid content of 25.6%. According to SEM-EDS testing, the average particle size of the emulsion is 285nm.
[0054] The PFA emulsion after the reaction was condensed, washed with water, and dried to obtain 1038g of PFA resin powder. The PFA melt index was measured to be 18.3g / 10min using a melt index meter, the melting point was measured to be 302°C using a differential scanning calorimeter DSC, and the TFE / PPVE content (mol ratio) in the PFA polymer was measured to be 96.9 / 3.1 using infrared FT-IR. The fluorine-containing emulsifier content in the PFA powder was tested to be 8.5ppb.
[0055] Example 3
[0056] Add 3L of deionized water, 6g of CF3OCF2CF2OCF(CF3)COONH4(a) aqueous solution with a mass concentration of 20% and 14g of CF3OCF2OCF2CF2OCF(CF3)COONH4(b) aqueous solution to a 5L stainless steel autoclave equipped with a stirring and temperature control device, and repeatedly evacuate and replace with nitrogen until the oxygen content is below 10ppm. Add 10g of methanol, heat to 60°C, add TFE to the system until the pressure reaches 2.0MPa, and add 48g of PPVE monomer with a metering pump. Add 10g of 2g / L ammonium persulfate solution to the polymerization kettle to initiate the polymerization reaction. After the reaction starts, continue to add TFE monomer and PPVE monomer to maintain the polymerization pressure at 2.0MPa, and continue to add ammonium persulfate solution at a rate of 0.15g / min. The polymerization reaction was stopped after 2.5 hours, wherein 96 g of PPVE monomer and 920 g of TFE monomer were added cumulatively, and the unreacted monomers in the reactor were vented to obtain an emulsion with a solid content of 26.4%. The average particle size of the emulsion was 278 nm as determined by SEM-EDS.
[0057] The PFA emulsion after the reaction was condensed, washed with water, and dried to obtain 1056g of PFA resin powder. The PFA melt index was measured to be 18.5g / 10min using a melt index meter, the melting point was measured to be 302°C using a differential scanning calorimeter DSC, and the TFE / PPVE content (mol ratio) in the PFA polymer was measured to be 97.2 / 2.8 using infrared FT-IR. The fluorine-containing emulsifier content in the PFA powder was tested to be 6.7ppb.
[0058] Example 4
[0059] Add 3L of deionized water and 16g of CF3CF2OCF(CF3)CF2OCF(CF3)COONH4(c) aqueous solution with a mass concentration of 20% to a 5L stainless steel autoclave equipped with a stirring and temperature control device, and repeatedly evacuate and replace with nitrogen until the oxygen content is below 10ppm. Add 10g of ethane, raise the temperature to 60°C, add TFE to the system until the pressure reaches 2.0MPa, and add 52g of PPVE monomer with a metering pump. Add 10g of 2g / L ammonium persulfate solution to the polymerization kettle to initiate the polymerization reaction. After the reaction starts, continue to add TFE monomer and PPVE monomer to maintain the polymerization pressure of 2.0MPa, and continue to add ammonium persulfate solution at a rate of 0.15g / min. The polymerization reaction is stopped after 2.5 hours. Among them, a total of 109g of PPVE monomer and 980g of TFE monomer are added, and the unreacted monomers in the kettle are vented to obtain an emulsion with a solid content of 28.4%. SEM-EDS test showed that the average particle size of the emulsion was 274 nm.
[0060] The PFA emulsion after the reaction was condensed, washed with water, and dried to obtain 1038g of PFA resin powder. The PFA melt index was measured to be 17.6g / 10min using a melt index meter, the melting point was measured to be 303°C using a differential scanning calorimeter DSC, and the TFE / PPVE content (mol ratio) in the polymer was measured to be 97.3 / 2.7 using infrared FT-IR combined with solid NMR. The fluorinated emulsifier content in the PFA powder was tested to be 4.8ppb.
[0061] Example 5
[0062] Add 3L of deionized water, 6g of CF3OCF2OCF2CF2OCF(CF3)COONH4(b) aqueous solution with a mass concentration of 20%, and 14g of CF3CF2OCF(CF3)CF2OCF(CF3)COONH4(c) aqueous solution to a 5L stainless steel autoclave equipped with a stirring and temperature control device, and repeatedly evacuate and replace with nitrogen until the oxygen content is below 10ppm. Add 10g of ethane, heat to 60°C, add TFE to the system until the pressure reaches 2.0MPa, and add 50g of PPVE monomer with a metering pump. Add 10g of 2g / L ammonium persulfate solution to the polymerization kettle to initiate the polymerization reaction. After the reaction starts, continue to add TFE monomer and PPVE monomer to maintain the polymerization pressure at 2.0MPa, and continue to add ammonium persulfate solution at a rate of 0.15g / min. The polymerization reaction stops after 2.5 hours. Among them, 96g of PPVE monomer and 925g of TFE monomer were added cumulatively, and the unreacted monomers in the kettle were vented to obtain an emulsion with a solid content of 26.1%. According to SEM-EDS testing, the average particle size of the emulsion was 263nm.
[0063] The PFA emulsion after the reaction was condensed, washed with water, and dried to obtain 1040 g of PFA resin powder. The PFA melt index was measured to be 19.5 g / 10 min using a melt index meter, the melting point was measured to be 303 ° C using a differential scanning calorimeter DSC, and the TFE / PPVE content (mol ratio) in the polymer was measured to be 96.8 / 3.2 using infrared FT-IR combined with solid NMR. The fluorinated emulsifier content in the PFA powder was tested to be 5.5 ppb.
[0064] Comparative Example 1
[0065] Add 3L of deionized water and 16g of 20% perfluorooctanoic acid ammonium CF3(CF2)6COONH4(PFOA) aqueous solution to a 5L stainless steel autoclave equipped with a stirring and temperature control device, and repeatedly evacuate and replace with nitrogen until the oxygen content is below 10ppm. Add 10g of methanol, heat to 60°C, add tetrafluoroethylene to the system until the pressure reaches 2.0MPa, and add 48g of PPVE monomer with a metering pump. Add 10g of 2g / L ammonium persulfate solution to the polymerization kettle to initiate the polymerization reaction. After the reaction starts, continue to add TFE monomer and PPVE monomer to maintain the polymerization pressure of 2.0MPa, and continue to add ammonium persulfate solution at a rate of 0.15g / min. The polymerization reaction was stopped after 2.5 hours, and 88g of PPVE monomer and 1045g of TFE monomer were added cumulatively. The unreacted monomers in the kettle were vented to obtain an emulsion with a solid content of 30.8%. According to SEM-EDS testing, the average particle size of the emulsion was 251nm.
[0066] The PFA emulsion after the reaction was condensed, washed with water, and dried to obtain 1167g of PFA resin powder. The PFA melt index was measured to be 13.5g / 10min using a melt index meter, the melting point was measured to be 302°C using a differential scanning calorimeter DSC, and the TFE / PPVE content (mol ratio) in the PFA polymer was measured to be 98.3 / 1.7 using infrared FT-IR. The fluorine-containing emulsifier content in the PFA powder was tested to be 75.5ppb.
[0067] Comparative Example 2
[0068] Add 3L of deionized water and 20g of 20% perfluorooctanoic acid ammonium CF3(CF2)6COONH4(PFOA) aqueous solution to a 5L stainless steel autoclave equipped with a stirring and temperature control device, and repeatedly evacuate and replace with nitrogen until the oxygen content is below 10ppm. Add 10g of ethane, heat to 60°C, add tetrafluoroethylene to the system until the pressure reaches 2.0MPa, and add 52g of PPVE monomer with a metering pump. Add 10g of 2g / L ammonium persulfate solution to the polymerization kettle to initiate the polymerization reaction. After the reaction starts, continue to add TFE monomer and PPVE monomer to maintain the polymerization pressure of 2.0MPa, and continue to add ammonium persulfate solution at a rate of 0.15g / min. The polymerization reaction stops after 2.5 hours. Among them, 131g of PPVE monomer and 1080g of TFE monomer were added cumulatively, and the unreacted monomers in the kettle were emptied to obtain an emulsion with a solid content of 30.4%. According to SEM-EDS testing, the average particle size of the emulsion is 259nm.
[0069] The PFA emulsion after the reaction was condensed, washed and dried to obtain 1271g of PFA resin powder. The PFA melt index was measured to be 15.2g / 10min using a melt index meter, the melting point was measured to be 301°C using a differential scanning calorimeter DSC, and the TFE / PEVE content (mol ratio) in the polymer was measured to be 98.4 / 1.6 using infrared FT-IR combined with solid NMR. The fluorinated emulsifier content in the PFA powder was tested to be 96.0ppb.
[0070] Comparative Example 3
[0071] Add 3L of deionized water and 20g of 20% CF3CF2OCF2CF2OCF2COONH4 (EEA) aqueous solution to a 5L stainless steel autoclave equipped with a stirring and temperature control device, and repeatedly evacuate and replace with nitrogen until the oxygen content is below 10ppm. Add 10g of methanol, heat to 60°C, add TFE to the system until the pressure reaches 2.0MPa, and add 48g of PPVE monomer with a metering pump. Add 10g of 2g / L ammonium persulfate solution to the polymerization kettle to initiate the polymerization reaction. After the reaction starts, continue to add TFE monomer and PPVE monomer to maintain the polymerization pressure of 2.0MPa, and continue to add ammonium persulfate solution at a rate of 0.15g / min. The polymerization reaction was stopped after 2.5 hours, during which 74g of PPVE monomer and 728g of TFE monomer were added cumulatively, and the unreacted monomers in the kettle were vented to obtain an emulsion with a solid content of 21.2%. According to SEM-EDS testing, the average particle size of the emulsion was 297nm.
[0072] The PFA emulsion after the reaction was condensed, washed with water, and dried to obtain 812g of PFA resin powder. The PFA melt index was measured to be 18.5g / 10min using a melt index meter, the melting point was measured to be 302°C using a differential scanning calorimeter DSC, and the TFE / PPVE content (mol ratio) in the PFA polymer was measured to be 98.5 / 1.5 using infrared FT-IR. The fluorine-containing emulsifier content in the PFA powder was tested to be 87.5ppb.
[0073] Comparative Example 4
[0074] Add 3L of deionized water and 20g of 20% CF3CF2CF2OCF(CF3)CF2OCF(CF3)COONH4(d) aqueous solution to a 5L stainless steel autoclave equipped with a stirring and temperature control device, and repeatedly evacuate and replace with nitrogen until the oxygen content is below 10ppm. Add 10g of methanol, raise the temperature to 60°C, add TFE to the system until the pressure reaches 2.0MPa, and add 52g of PEVE monomer with a metering pump. Add 10g of 2g / L ammonium persulfate solution to the polymerization kettle to initiate the polymerization reaction. After the reaction starts, continue to add TFE monomer and PPVE monomer to maintain the polymerization pressure of 2.0MPa, and continue to add ammonium persulfate solution at a rate of 0.15g / min. The polymerization reaction was stopped after 2.5 hours, during which 86g of PEVE monomer and 720g of TFE monomer were added cumulatively, and the unreacted monomers in the kettle were vented to obtain an emulsion with a solid content of 22.8%. According to SEM-EDS test, the average particle size of the emulsion is 298nm.
[0075] The PFA emulsion after the reaction was condensed, washed and dried to obtain 833g of PFA resin powder. The PFA melt index was measured to be 21.6g / 10min using a melt index meter, the melting point was measured to be 252°C using a differential scanning calorimeter DSC, and the TFE / PPVE content (mol ratio) in the polymer was measured to be 97.7 / 2.3 using infrared FT-IR combined with solid NMR. The fluorinated emulsifier content in the PFA powder was tested to be 96.5ppb.
[0076] The results of each example and comparative example are summarized in Table 1.
[0077] Table 1
[0078]
[0079]
Claims
1. A tetrafluoroethylene and perfluoroalkyl vinyl ether copolymer resin, characterized in that: It comprises tetrafluoroethylene structural units (TFE units) and perfluoroalkyl vinyl ether structural units (PAVE units), wherein the molar ratio of the TFE units to the PAVE units is 70-99.5 / 30-0.5; The resin is prepared by copolymerizing tetrafluoroethylene and PAVE monomers in an aqueous medium using a fluorinated emulsifier represented by formula (1), and then condensing, washing and drying the emulsion. The residual amount of the fluorinated emulsifier represented by formula (1) in the resin is less than 0.2 ppm. The emulsifier structure is shown in the general formula (1): f1 (OCF2) x -(OR f2 ) y -OCF(CF3)COOA, in formula (1), the R f1 is a perfluoro straight-chain alkyl group having 1 to 2 carbon atoms, R f2 It is a perfluorinated straight chain or side chain alkyl group having 2 to 3 carbon atoms, x and y are each independently 0 or 1, and x and y are not simultaneously 0, and A is a hydrogen atom, an alkali metal or NH4.
2. The resin according to claim 1, characterized in that In formula (1), A is NH4.
3. The resin according to claim 1, characterized in that The residual amount of emulsifier in the fluororesin is less than 50ppb.
4. The resin according to claim 1, characterized in that The residual amount of emulsifier in fluororesin is less than 25ppb.
5. The resin according to claim 1, characterized in that The fluorinated emulsifier is (a)CF3OCF2CF2OCF(CF3)COONH4, (b)CF3OCF2OCF2CF2OCF(CF3)COONH4, (c) one or a combination of CF3CF2OCF(CF3)CF2OCF(CF3)COONH4.
6. The resin according to claim 1, characterized in that The molar ratio of TFE units to PAVE units in the resin is 96-98 / 2-4.
7. The resin according to claim 1, characterized in that The PFA resin has a melt index of 1 to 30 g / 10 min, and an emulsion particle size of 250 to 290 nm.
8. The method for preparing the resin according to any one of claims 1 to 7, characterized in that: The following steps are involved: In the presence of an aqueous medium, an emulsifier, a free radical polymerization initiator and a molecular weight regulator, TFE and PAVE copolymer monomers are emulsion polymerized, and the prepared copolymer emulsion is subjected to coagulation, washing and drying steps to obtain PFA resin powder.
9. The preparation method according to claim 8, characterized in that: The amount of the emulsifier used is 500-15000 ppm based on the mass of the PFA polymer finally obtained.
10. The preparation method according to claim 9, characterized in that: The amount of the emulsifier used is 2000 to 10000 ppm based on the mass of the PFA polymer finally obtained.
Citation Information
Patent Citations
Fluororesin with low fluorine-containing emulsifier residual and method for producing same
CN101296950A
Ethylene-tetrafluoroethylene carboxylic acid and salt
CN102264684A
Method for producing aqueous polytetrafluoroethylene dispersion
CN106084104A
Emulsifier free aqueous emulsion polymerization process for making fluoropolymers
CN1505644A
Method for producing polytetrafluoroethylene fine powder
CN104093747A
Cited By
High-speed transmission lotus root core wire and preparation method thereof
CN121641556A